Pengembangan Media Pembelajaran E-Modul Pekerjaan Dasar Teknik Mesin untuk siswa SMK - Maftakhur Rizqi Ahmadi; Nurmida Catherine Sitompul; Hartono Hartono (Jurnal Pendidikan Edutama, 2022)
Abstract: Development of teaching materials is a process to produce innovation in teaching and learning activities. The research aims to produce learning products in the form of electronic modules in the subject of Basic Mechanical Engineering Work. Develop learning media in the form of e-modules whose contents are not just basic concepts of mechanical engineering vocational competence, but images, sounds, animations and videos will also be displayed so that students can more easily understand the material being taught and can increase students' attention to the material. being taught. The research subjects were students of class X Welding Engineering Department at SMK Negeri 2 Lamongan. Product development of teaching materials for basic work Mechanical engineering is a research and development (R & D) model of Dick & Carey. The results of the research are learning products in the form of e-modules that have gone through a feasibility test involving reviews of experts, namely material experts, learning design experts and media experts as well as feasibility tests through peer trials, small groups and field tests. The formative evaluation shows that this product is classified as "good", so it can be used as a support for teachers in teaching and learning activities using this E-Module, teachers can apply a combination of face-to-face learning at school and distance learning. Students can learn independently by using EModul without being limited by space and time. Keywords: e-module, Basic Mechanical Engineering Work, Development Research, Teaching Materials, Vocational Education  Abstrak: Pengembangan bahan ajar adalah suatu proses untuk menghasilkan inovasi dalam kegiatan belajar mengajar. Penelitian bertujuan untuk menghasilkan produk pembelajaran dalam bentuk modul elektronik pada mata pelajaran Pekerjaan Dasar Teknik mesin. Pembangkan media pembelajaran dalam bentuk e-modul yang isinya bukan sekedar konsep-konsep dasar kompetensi kejuruan teknik mesin, tetapi akan ditampilkan juga gambar, suara, animasi dan video sehingga peserta didik dapat lebih mudah memahami materi yang diajarkan serta dapat meningkatkan perhatian peserta didik terhadap materi yang diajarkan. Subjek penelitian adalah siswa kelas X Jurusan Teknik Pengelasan di SMK Negeri 2 Lamongan. Pengembangan produk bahan ajar pekerjaan dasar Teknik mesin merupakan penelitian pengembangan (R & D) model Dick & Carey. Hasil penelitian adalah produk pembelajaran dalam bentuk e-modul yang telah melalui uji kelayakan yang melibatkan review para ahli, yaitu ahli materi, ahli desain pembelajaran dan ahli media serta uji kelayakan melalui uji coba teman sejawat, small group dan field test. Evaluasi formatif menunjukkan, produk ini tergolong "baik", sehingga dapat digunakan sebagai penunjang bagi guru dalam kegiatan belajar mengajar dengan menggunakan E-Modul ini guru dapat menerapkan pembelajaran kombinasi antara tatap muka di sekolah dan pembelajaran jarak jauh. Siswa dapat belajar mandiri dengan menggunakan E-Modul tanpa dibatasi ruang dan waktu. Kata Kunci: e-modul, Pekerjaan Dasar Teknik Mesin, Penelitian Pengembangan, Bahan Ajar, Pendidikan Vokasi